2012
DOI: 10.1186/1471-2334-12-93
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of avian influenza A (H5N1) virus among poultry workers in Jiangsu Province, China: an observational study

Abstract: BackgroundSince 2003 to 06 Jan 2012, the number of laboratory confirmed human cases of infection with avian influenza in China was 41 and 27 were fatal. However, the official estimate of the H5N1 case-fatality rate has been described by some as an over estimation since there may be numerous undetected asymptomatic/mild cases of H5N1 infection. This study was conducted to better understand the real infection rate and evaluate the potential risk factors for the zoonotic spread of H5N1 viruses to humans.MethodsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 9 publications
0
15
1
Order By: Relevance
“…Low rates of subclinical infection in poultry (chickens of domestic waterfowl) workers have previously been documented in a number of Chinese studies [28], [29]. In addition, studies conducted in other countries have also reported low frequency of transmission of this virus to poultry (chickens of domestic waterfowl) workers [30][32].…”
Section: Discussionmentioning
confidence: 87%
“…Low rates of subclinical infection in poultry (chickens of domestic waterfowl) workers have previously been documented in a number of Chinese studies [28], [29]. In addition, studies conducted in other countries have also reported low frequency of transmission of this virus to poultry (chickens of domestic waterfowl) workers [30][32].…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that transmission of other H5 viruses from infected birds to humans has rarely occurred in Europe, Asia, and Africa ( 10 , 22 , 23 ). Exposures in those studies also likely occurred in a different context in many circumstances and may have had higher transmission likelihood than the exposures described in this report.…”
Section: Discussionmentioning
confidence: 99%
“…XiangHuo [20] reported that the overall seropositive rate was 2.61% for H5N1 antibodies among poultry workers in Jiangsu, China. The wild migratory birds might be identified as a risk factor for human infection with AIV H5.…”
Section: Discussionmentioning
confidence: 99%